2022
DOI: 10.3389/fmicb.2022.961498
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo synergistic effect of chrysin in combination with colistin against Acinetobacter baumannii

Abstract: Acinetobacter baumannii is an opportunistic pathogen that is primarily associated with nosocomial infections. With the rise in cases of acquired drug resistance, A. baumannii is gaining resistance to conventional antimicrobial drugs and even to the last line of antibiotics, such as colistin. Hence, the application of the synergistic combination of an antibiotic and a non-antibacterial agent is being contemplated as a new alternative therapeutic approach. Chrysin is a component of honey with anti-inflammatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Cytotoxicity analyses also confirmed the excellent biosafety profile of this combination treatment regimen. Analyses of the potential mechanism of action whereby FFA sensitizes cells to colistin were performed using membrane permeability assays with propidium iodide (PI), which showed that FFA may induce damage to the bacterial membrane, thereby enhancing the antibacterial efficacy of colistin ( 31 33 ). These findings demonstrated the potential of this combination for in vivo use in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity analyses also confirmed the excellent biosafety profile of this combination treatment regimen. Analyses of the potential mechanism of action whereby FFA sensitizes cells to colistin were performed using membrane permeability assays with propidium iodide (PI), which showed that FFA may induce damage to the bacterial membrane, thereby enhancing the antibacterial efficacy of colistin ( 31 33 ). These findings demonstrated the potential of this combination for in vivo use in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of azomycin and azomycin–colistin was evaluated using the RBC hemolysis test and cytotoxicity test . Briefly, erythrocytes collected from healthy male mice were used to prepare a 5% erythrocyte suspension with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…The safety of azomycin and azomycin−colistin was evaluated using the RBC hemolysis test 34 and cytotoxicity test. 35 Briefly, erythrocytes collected from healthy male mice were used to prepare a 5% erythrocyte suspension with PBS. Azomycin (1 to 64 μg/mL) was added for the experimental group, whereas DMSO (1−5%) was added for the solvent control group.…”
Section: ■ Methodsmentioning
confidence: 99%
See 2 more Smart Citations